Variations in gender and age perceptions of mobile technology enhanced learning in a New Zealand tertiary institution - Snell, Sarah (Curtin University, 2012)
The major purpose of this study was to investigate students' actual and preferred perceptions of a mobile enhanced learning environment at a tertiary institution in New Zealand and if these variations in perceptions differed based on gender and age. In order for this to be achieved, a new learning environment instrument was developed based on modifying the existing Web-based Learning Environment Instrument (WEBLEI) with scale items being modified to create the Mobile Enhanced Learning Environment Instrument (MOBLEI). A review of the literature examined learning environments and questionnaires on which the theoretical framework for this study was based. The use of mobile technologies in learning environments was provided along with a discussion around gender and age and differences between males and females and generational groups in relation to learning and technology.Students’ perceptions of their learning environment were determined through the use of qualitative and quantitative methods with open-ended questions being included in the MOBLEI, along with follow up focus groups. The MOBLEI was distributed to 141 tertiary business and computing students, and was found to be a valid and reliable tool for application in a tertiary environment in New Zealand. Results from the MOBLEI showed no significant differences between the perceptions of males and females, however younger age groups had a more positive attitude toward the use of technology than did their more mature counterparts. Overall, the study provided an insight into how students perceive a mobile enhanced learning environment, along with practical implications for education practitioners with an aim to provide direction for an ideal mobile enhanced learning environment for education practitioners in the tertiary environment.